Reflexões sobre o Programa Nacional Escolas Sustentáveis - Bastos, Daniela Botti Dias (2016)
This study has had as purpose analysing the Programa Nacional Escolas Sustentáveis – PNES [Sustainable Schools National Programme] and its applications, germane to the criteria of the law n.º 9795, from 27th April, 1999, which ordain about Educação Ambiental - EA [Environmental Education]. Therefore, considerations have been conducted about the concepts of Sustainable School and the Programa Dinheiro Direto na Escola – PDDE [Money Directly into the School Programme], as well as the relevance of the formation groups on the effectuation of discussions about Environmental Education. To develop this analysis, interviews were carried out with environmental educators and environmental education managers who have taken part on the formation and development of this programme, in which they were able to present their opinions about the affirmative actions of implementation and the predicaments addressed for its effectuation, having assessed the aspects that have weakened its national structure. Considering the idea of transforming the awareness of the environment starting from the schools , according to the concept of Sustainable Schools , the Programme presents itself as innovative , but not found is consolidated as a public politics for lack of institutional support , undermining its applicability , evaluation and continuity.